2005
DOI: 10.1029/2004jd005265
|View full text |Cite
|
Sign up to set email alerts
|

Toward the development of a diffuse horizontal shortwave irradiance working standard

Abstract: [1] The first intensive observation period (IOP) to simultaneously measure diffuse horizontal shortwave irradiance (scattered solar radiation that falls on a horizontal surface) with a wide array of shaded pyranometers suggested that a consensus might be reached that would permit the establishment of a standard with a smaller uncertainty than previously achieved. A second IOP has been held to refine the first IOP measurements using a uniform calibration protocol, offset corrections for all instruments and vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 13 publications
3
28
0
Order By: Relevance
“…This monitoring is performed until the detector has responded to the SW blocking but before the dome temperature changes significantly. This is a reliable procedure, since the dome temperature has a time constant that is distinguishably longer than the detector (several minutes vs a few seconds) (Bush et al 2000;Dutton et al 2001;Haeffelin et al 2001;Michalsky et al 2005;Carlund 2013). Its main drawback is the possible effect of the capping on the thermal balance due to the cap emission and the alteration of the circulation of the air (Ji and Tsay 2010).…”
Section: A Technique For Measuring the Thermal Offsetmentioning
confidence: 98%
“…This monitoring is performed until the detector has responded to the SW blocking but before the dome temperature changes significantly. This is a reliable procedure, since the dome temperature has a time constant that is distinguishably longer than the detector (several minutes vs a few seconds) (Bush et al 2000;Dutton et al 2001;Haeffelin et al 2001;Michalsky et al 2005;Carlund 2013). Its main drawback is the possible effect of the capping on the thermal balance due to the cap emission and the alteration of the circulation of the air (Ji and Tsay 2010).…”
Section: A Technique For Measuring the Thermal Offsetmentioning
confidence: 98%
“…Various studies have been published to evaluate the comparative performance of various types of radiometers [4,24,36,62,64,101]. Such studies can help make sound decisions about the most appropriate type and brand of sensor to buy depending on the specificities of each project including budget.…”
Section: Specific Considerations For Solar Resource Assessmentmentioning
confidence: 98%
“…Early studies demonstrated that broadband shortwave direct irradiance models and measurements were in agreement to better than 1%, but model calculations of the diffuse flux were typically high by 10s of percents, sometimes off by as much as 30 W m -2 (Halthore et al 1998;Kato et al 1997). Additional research results, primarily impacting the actual measurements of diffuse shortwave radiation, have reduced this difference to about 10% or 7-10 W m -2 (Cess et al 2000;Dutton et al 2001;Michalsky et al 1999Michalsky et al , 2004Philipona 2002;Younkin and Long, 2004).…”
Section: Atmospheric Radiative Sciencementioning
confidence: 99%